The Tax-Efficient Use of Debt in Multinational Corporations - Jarle Møen; Dirk Schindler; Guttorm Schjelderup; Georg Wamser (Center for Economic Studies and ifo Institute (CESifo), 2018)
Some multinationals use the parent company as a lender to the group, whereas others set up an internal bank in a low tax jurisdiction. This paper discusses the link between capital structure choices and tax planning motives in multinational groups. We model the trade-off between the use of external debt, parental debt and an internal bank. We test the theory model using data on the universe of German multinationals. The empirical analysis largely supports our model in that: (i) smaller firms often rely on parental debt financing; (ii) larger multinationals are more likely to use internal banks; (iii) parental debt and external debt are substitutes and the mix depends on the relative cost of raising capital through the parent and the affiliates; (iv) both parental debt and external debt increase when the tax rate increases, all else equal.
Keywords: H25; G32; F23; 330; corporate taxation; multinationals; capital structure; international debt-shifting; parental debt